Process intensification: New understanding and systematic approach - Ponce-Ortega, José María; Al-Thubaiti, Musaed M.; El-Halwagi, Mahmoud M. (Chemical engineering and processing, 2012)
► This paper presents new definitions for process intensification. ► General mathematical programming formulations for intensification are proposed. ► Process integration techniques are very useful for process intensification. ► The main objectives for process intensification are identified and explained. ► Results show the advantages for the new definitions of process intensification. This paper presents new definitions for process intensification identifying two main categories called unit intensification and plant intensification. This paper also proposes general mathematical programming formulations for the different categories of intensification through a disjunctive formulation to consider the use of existing units or to include additional units. The ideas of process integration (energy, mass and property integration) are very useful for process intensification helping in maximizing throughput for a given process, minimizing process inventory for a given throughput or in minimizing utilities and feedstock for a given throughput (this means that process intensification is broader than process integration). This paper identifies that process intensification is a wider approach than single unit intensification as it was considered by most of the previous works. A case study is presented to show the applicability of the proposed models and definitions.